Wattage-independent dynamic conductance model of compact fluorescent lamps: Validation and application in high-frequency operation. (November 2018) - Gupta Bakshi, B; Roy, B
A wattage-independent (7–18 W) compact fluorescent lamp (CFL) model has been developed in Matlab-Simulink and validated in low-frequency (50 Hz) operation in our earlier work. In this paper, the same lamp model is simulated for high-frequency operation and then validated experimentally with a 9 W test CFL driven by a compatible electronic ballast (e-ballast). Simulation results have shown a maximum 6.4% deviation compared to the measured data. Thereafter, the developed model is applied to obtain the arc resistance versus power and power versus frequency characteristics of CFLs required to design dimmable e-ballasts. An algorithm is developed to compute design parameters of a dimmable e-ballast based on voltage-fed series-parallel resonant inverter topology. The electrical performance of the designed e-ballast is simulated at three different power levels (100%, 75% and 50%) using Matlab-Simulink.